Gap Analysis of Key Development Issues for Sustainable Development in Northern Thailand - Sitthisuntikul, Katesuda; Kaewthip, Somkid; Kavichai, Pongsakorn; Pattanapaiwan, Suwichan; Ongla, Olan (Thammasat Journal, 2024)
This study aimed to explore key development issues in Northern Thailand under sustainable development goals and to conduct a gap analysis on these issues to establish research directions for sustainable development in the region. To identify key development issues, document analysis was used to develop questionnaires addressing the economy, society, and environment. Forty questionnaires completed by experts were analyzed to prioritize key development issues based on significance scores. The significance score was calculated as the average of severity score plus the average of the impact score minus the average of the policy effectiveness score and the average of the policy adequacy score. A workshop was also organized to verify, discuss, and conclude the key development issues with experts. In addition, document analysis was used for the gap analysis of the key development issues, which were classified into knowledge discovered, knowledge required, and research directions for development. Another workshop was organized to verify, discuss, and conclude the gap analysis with experts. The result indicated four key development issues and their research directions: 1) resource allocation and community economy – database updates of resources and agricultural systems, decentralization of resource management, adaptation of the young generation to agricultural sector, innovation in processing and distributing agricultural products, and the development of a learning ecosystem; 2) PM, forest fire, and environment – database updates of PM, policy and decentralization of resource management, land management to reduce forest fires, and establishing cooperation with Asian countries; 3) good governance – policy obstacles, good governance law and decentralization, participatory action research for developing a prototype area of decentralization to local community, and good governance; and 4) education system - policy and structure of education, participatory action research for learning how to develop communities, use of technology for learning innovation, suitable educational design for communities, and the development of education personnel.